Long non-coding RNAs as prognostic biomarkers in non-muscle invasive bladder cancer: A systematic review - Hendri, Ahmad Z.; Suryawati, Sri; Heriyanto, Didik S.; Hardianti, Mardiah S.; Pikatan, Narpati W.; Shaleh, Sabillal; Robert, Robert; Febriyanto, Toni; Liliana, Belinda; Pratama, Angga DM. (Narra J, 2024)
Traditional prognostic tools for non-muscle invasive bladder cancer (NMIBC) often overestimate progression and recurrence risks, underscoring the need for more precise biomarkers. While long non-coding ribonucleic acids (lncRNAs) have been reviewed in bladder cancer, no review has focused on NMIBC. The aim of this study was to address this gap by investigating the role of lncRNAs in predicting NMIBC survival and progression. A systematic review was conducted using PubMed, Scopus, and Cochrane databases as of July 31, 2024. Prognostic studies investigating the association between lncRNA expression and survival outcomes, such as cancer-specific survival, disease-free survival, recurrence-free survival, or overall survival, using Kaplan-Meier curves or hazard ratios, were included. A total of three studies were analyzed, involving 279 NMIBC patients and focusing on three lncRNAs: urothelial cancer associated 1 (UCA1), growth arrest-specific 5 (GAS5), and up-regulated in non-muscle invasive bladder cancer (UNMIBC). Increased UCA1 expression was strongly associated with poor disease-free survival (hazard ratio (HR): 1.974; 95%CI: 1.061–3.673; p=0.032) and progression-free survival (HR: 3.476; 95%CI: 1.187–10.18; p=0.023). Reduced GAS5 expression was significantly associated with poor disease-free survival (HR: 2.659; 95%CI: 1.348–5.576; p=0.005) and progression-free survival (HR: 6.628; 95%CI: 1.494–29.40; p=0.013). Higher level of UNMIBC was strongly associated with poor recurrence-free survival (HR: 2.362; 95%CI: 1.504–4.837; p=0.007). In conclusion, lncRNAs have potential as prognostic biomarkers in NMIBC, with UCA1 and UNMIBC overexpression and GAS5 underexpression being significant in predicting disease recurrence and progression, highlighting the clinical relevance of monitoring these lncRNAs to improve prognosis and guide treatment decisions.